2009
DOI: 10.1093/jnci/djp058
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse-Type Gastric Carcinoma: Progression, Angiogenesis, and Transforming Growth Factor β Signaling

Abstract: BackgroundDiffuse-type gastric carcinoma is a cancer with poor prognosis that has high levels of transforming growth factor β (TGF-β) expression and thick stromal fibrosis. However, the association of TGF-β signaling with diffuse-type gastric carcinoma has not been investigated in detail.MethodsWe used a lentiviral infection system to express a dominant-negative TGF-β type II receptor (dnTβRII) or green fluorescent protein (GFP) as a control in the diffuse-type gastric carcinoma cell lines, OCUM-2MLN and OCUM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 34 publications
5
76
0
3
Order By: Relevance
“…Tumor growth of diffuse-type gastric carcinoma OCUM-2MLN cells is reported to be enhanced by inhibition of the TGF-b signaling pathway in cancer cells (Kiyono et al, 2009;Komuro et al, 2009). In accordance with these reports, TGF-b-induced phosphorylation of Smad2 was completely inhibited in OCUM-2MLN cells, which stably expressed dominant negative form of TbRII (2MLN-dnTbRII), but not in control cells, which expressed green fluorescent protein (2MLN-GFP) (Figure 1a).…”
Section: Cics Are Enriched In 2mln-dntbrii Cellssupporting
confidence: 79%
See 2 more Smart Citations
“…Tumor growth of diffuse-type gastric carcinoma OCUM-2MLN cells is reported to be enhanced by inhibition of the TGF-b signaling pathway in cancer cells (Kiyono et al, 2009;Komuro et al, 2009). In accordance with these reports, TGF-b-induced phosphorylation of Smad2 was completely inhibited in OCUM-2MLN cells, which stably expressed dominant negative form of TbRII (2MLN-dnTbRII), but not in control cells, which expressed green fluorescent protein (2MLN-GFP) (Figure 1a).…”
Section: Cics Are Enriched In 2mln-dntbrii Cellssupporting
confidence: 79%
“…We previously reported that deregulation of the TGFb signaling pathway in the diffuse-type gastric carcinoma OCUM-2MLN cells, which were derived from lymph node metastasis of orthotopically implanted primary carcinoma cells, promotes the growth of primary tumors in mouse xenograft models through acceleration of angiogenesis (Kiyono et al, 2009;Komuro et al, 2009). In addition to this mechanism, we here present evidence that TGF-b has a novel role in regulation of the maintenance of CICs in diffuse-type gastric carcinoma cells.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…A previous study has identified that upregulation of the miR-106b/miR-93/miR-25 cluster impairs G 1 /S arrest and apoptosis in GC cells and that this is associated with TGFb signaling (Petrocca et al, 2008). Disruption in TGFb signaling facilitates the growth of diffuse-type GC (Komuro et al, 2009). Furthermore, TGFb suppresses the progression of diffuse-type GC by inducing the differentiation of cancer-initiating cell sub-population (Ehata et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…SB431542 blocks Smad signaling by inactivating TGFb1-RI receptor kinase (Inman et al, 2002). Impairment of TGFb signaling in GC models appeared to accelerate tumor growth (Komuro et al, 2009) and resistance to the TGFb suppressor seems to be an important event in gastric carcinogenesis (Ju et al, 2003). A recent study has shown that E2F2 upregulates the expression of the miR-106b-25 polycistronic cluster, which targets TGFb signaling and enhances gastric carcinogenesis (Petrocca et al, 2008).…”
Section: Introductionmentioning
confidence: 99%